Protopolybia aliciae, a new polistine social wasp from Brazilian Amazonia (Hym.; Vespidae, Polistinae, Epiponini) - Silveira, Orlando Tobias (Zootaxa, 2004)
A description and photographs of Protopolybia aliciae are presented, a new swarming species of social polistine wasp from the Brazilian state of Pari.